Accreditation in India: Pathways and Mechanisms. Issue 1 (1st January 2018) - Das, Swaptagni; Shah, Manan; Mane, Amey; Goyal, Vishal; Singh, Vikram; Lele, Jayesh
ABSTRACT: Continuing medical education (CME) is a valuable mechanism to update physicians' knowledge with ever-increasing plethora of contemporary advances within medical fraternity. Over time, scope of CME has seen change from simple clinical updates to comprehensive continuing professional development (CPD), which is accomplished with help of accredited CME programmes. The Medical Council of India, in 2011, made a mandatory resolution for doctors to attend minimum of 30 hours of CME/5 years to ensure recertification. Authorised accreditation councils and licensing authorities award CME credits for maintenance of physicians' licensures. To date, in India, only 9 of 26 State Medical Councils have made re-registration mandatory. Although CME events benefit healthcare professionals by improving their proficiency and awareness, costs even to attend such interventions may be prohibitive. Despite financial help being received through grants and sponsorships, ethics of industry-sponsored CME remains a matter of debate. However, over past 10 years, pharmaceutical companies have started going beyond basic product information in order to focus on building physicians' knowledge in various therapeutic areas. Though CME credit system and criteria for re-licensure for medical practice in India are evolving at a rapid pace, there is a need for harmonisation and robust implementation across all states in India.